Teaching Strategies in Physics Education: A Systematic Literature Review - Tomas Jr Diquito; Risanti Dhaniaputri; Alliesa R. Acuña (Postgraduate, University of Mataram, 2025)
Physics is a complex science discipline that intertwined with other disciplines (e.g. chemistry, life sciences, and mathematics), making it challenging for other learners to learn. To cope, educators developed strategies tailored to the needs of learners and their context. This article conducts a comprehensive systematic literature review of research articles available in Google Scholar that focuses on the concept of innovative strategies in teaching physics. Guided by the PRISMA model, 119 articles were identified, and of these, 31 articles were deemed relevant to the study. The result shows that the most used method in developing teaching strategies in physics is quasi-experimental followed by research and development. Result shows that physics education strategies are the most explored topic followed by physics laboratory innovations. Moreover, the recently published articles can be classified into two themes: non-digital teaching strategy and technology-aided teaching strategy. Outcomes of these developed strategies have shown improved learning among students and the development/enhancement of skills necessary in the 21st century such as problem-solving, analytical thinking, visualization, and social skills. Thus, this shows that the innovation of methodology-oriented new teaching strategies to address challenges in learning physics is crucial for improving conceptual understanding among learners.